Cytochrome P450-Based Drug-Drug Interactions of Vonoprazan In Vitro and In Vivo - Wang, Yiran; Wang, Changxiong; Wang, Shuanghu; Zhou, Quan; Dai, Dapeng; Shi, Jihua; Xu, Xue; Luo, Qingfeng (Frontiers in Pharmacology, 2020)
Background: Vonoprazan fumarate is a potassium-competitive acid blocker that was developed as a novel acid-suppressing drug for multiple indications. As a potential alternative to proton-pump inhibitors, the determination of the drug-drug interactions is vital for further applications. Probe drug cocktails are a type of rapid, economical and efficient approach for evaluating cytochrome P450 enzyme activities. Since vonoprazan is metabolized partly by cytochrome P450, cocktails were used to study CYP-based drug-drug interactions. Methods: This study was conducted both in vitro and in vivo. In the in vitro study of rat liver microsomes, ultra-performance liquid chromatography coupled to tandem mass spectrometry was utilized to assess the reversible inhibition of cytochrome P450 by vonoprazan by determining the concentration of probe drugs (phenacetin, bupropion, tolbutamide, dextromethorphan, midazolam, chlorzaoxazone). The differences in the levels of probe drugs between the rat groups with or without vonoprazan administration were also tested in the rats. Results: In vitro analysis revealed that the IC50 values of midazolam, tolbutamide, dextromethorphan, and bupropion in rat microsomes were 22.48 μM, 18.34μM, 3.62μM, and 3.68μM, respectively, while chlorzoxazone and phenacetin displayed no inhibition. In vivo analysis revealed that midazolam, bupropion, dextromethorphan, and tolbutamide showed significant (P<0.05) differences in distinct pharmacokinetic parameters after vonoprazan administration, while those of chlorzoxazone and phenacetin were not significantly different. Conclusion: The in vitro and in vivo results indicated that vonoprazan can inhibit CYP3A4, CYP2C9, CYP2D6 and CYP2B6, suggesting that the coadministration of vonoprazan with cytochrome P450 substrates should be performed cautiously in clinical settings.